Conserved role for the Drosophila Pax6 homolog Eyeless in differentiation and function of insulin-producing neurons. - Clements, J; Hens, K; Francis, C; Schellens, A; Callaerts, P (2008)
Insulin/insulin-like growth factor (IGF) signaling constitutes an evolutionarily conserved pathway that controls growth, energy homeostasis, and longevity. In Drosophila melanogaster, key components of this pathway are the insulin-like peptides (Dilps). The major source of Dilps is a cluster of large neurons in the brain, the insulin-producing cells (IPCs). The genetic control of IPC development and function is poorly understood. Here, we demonstrate that the Pax6 homolog Eyeless is required in the IPCs to control their differentiation and function. Loss of eyeless results in phenotypes associated with loss of insulin signaling, including decreased animal size and increased carbohydrate levels in larval hemolymph. We show that mutations in eyeless lead to defective differentiation and morphologically abnormal IPCs. We also demonstrate that Eyeless controls IPC function by the direct transcriptional control of one of the major Dilps, dilp5. We propose that Eyeless has an evolutionarily conserved role in IPCs with remarkable similarities to the role of vertebrate Pax6 in beta cells of the pancreas.